The Relationship Between Price and Location with the Interest of the Academic Community of FPP Laundry at Unp Hospitality Laundry - M. Abdul Rahman; Retnaningtyas Susanti (Journal of Multidimensional Management, 2025)
This study investigates the influence of price and location on purchase intention in the context of UNP Hospitality Laundry, Indonesia. Using a quantitative approach, data were collected from 150 respondents through purposive sampling and analyzed using descriptive statistics, classical assumption tests, and multiple regression analysis. Results reveal that both price and location have positive and significant effects on purchase intention, with price showing a slightly stronger standardized coefficient. These findings support the Price–Value Theory and Location Theory, emphasizing that competitive pricing aligned with perceived quality, along with strategic and accessible location, are critical determinants of consumer decision-making in service industries. Theoretically, this research extends the application of these theories to the hospitality laundry sector, a relatively underexplored service niche in emerging markets. Practically, the results suggest that service providers should maintain price–quality alignment, improve price accessibility, and enhance location visibility beyond regular operational hours to attract more customers. For hospitality managers, integrating competitive pricing strategies with location-based service improvements may increase customer purchase intention and strengthen market competitiveness. Future studies could incorporate additional variables such as service quality, customer satisfaction, and brand image to provide a more comprehensive understanding of purchase behavior in hospitality services.